Diiron Azamonothiolates by the Scission of Dithiadiazacyclooctanes by Iron Carbonyls - Lin, Tai; Ulloa, Olbelina A.; Rauchfuss, Thomas B.; Gray, Danielle L. (European journal of inorganic chemistry, 2014)
The reactions of [Fe3(CO)12] with the dithiadiazacyclooctanes [SCH2N(R)CH2]2 (R = Me, Bn) afford the diiron complexes [Fe2{SCH2N(R)CH2}(CO)6] (1Me, 1Bu). The methyl derivative 1Me was characterized crystallographically [Fe–Fe = 2.5702(5) Å]. Its low symmetry was verified by variable‐temperature 13C NMR spectroscopy, which revealed that the turnstile rotation of the {S(CH2)Fe(CO)3} and {S(NMe)Fe(CO)3} centers are subject to very different energy barriers. Although 1Me resists protonation, it readily undergoes substitution by tertiary phosphines, first at the {S(CH2)Fe(CO)3} center, as verified crystallographically for [Fe2{SCH2N(Me)CH2}(CO)5(PPh3)]. Substitution by the chelating diphosphine Ph2PCH2CH2PPh2 (dppe) gave [Fe2{SCH2N(Me)CH2}(CO)4(dppe)] by substitution at both the {S(CH2)Fe(CO)3} and {S(NMe)Fe(CO)3} sites. It has long been known that Fe0 reagents activate many organosulfur compounds by scission of C–S bonds. Here, we report that S2N2 heterocycles undergo smooth activation by [Fe3(CO)12] to give azamonothiolates, not the well precedented azadithiolates. In these azathiolate complexes, all six CO ligands are diastereotopic.